The Use of Textbook Entitled “Let’s Learn English”: Teacher’s Overview - Muktamir Muktamir (Jurnal Pendidikan Edutama, 2020)
Abstract: Although there are some research revealing the evaluation of textbook used by the teacher, but a study investigating the use of textbook entitled “Let’s Learn English” as an instructional material viewed from teachers point of view were rare in number. The current study aimed at investigating the the use of textbook entitled “Let’s Learn English” as instructional material viewed from teacher’s perspective as the user. This study used the qualitative case study. The case study was intended to analyze the use of textbook entitled “Let’s Learn English”. The participants of this study was the teacher as the user. Text book analysis used was adapted from Mukundan & Nimehchisalem (2010). The results revealed that textbook entitled “Let’s Learn English” is applicable as an instructional material. Further research in evaluating the effectiveness of textbook entitled “Let’s Learn English” should be taken into account by the related parties.  Keywords: textbook evaluation, Textbook entitled “Let’s Learn English” Abstrak: Meskipun terdapat beberapa penelitian mengkaji tentang evaluasi buku teks yang digunakan oleh guru, namun sebuah penelitian yang bertujuan menginvestigasi penggunaan buku teks berjudul “Let’s Leran English”sebagai sumber pembelajaran dilihat dari sudut pandang guru belum pernah dilkasanakan. Penelitian ini bertujuan untuk menginvestigasi penggunaan buku teks berjudul “Let’s Learn English” sebagai sumber bahan ajar dilihat dari sudt pandang pendapat guru sebagai pengguna. Penelitian ini menggunakan metode kulaitatif studi kasus. Penelitian studi kasus bertujuan utuk menganalisis penggunaan buku teks berjudul Let’s Learn English”. Partisipan dalam penelitian ini adalah guru sebagai pengguna. Dalam analisis buku teks ini menggunakan analisis buku teks nya (Mukundan & Nimehchisalem, 2010). Hasil dari penelitian ini menunjukkan bahwa buku teks berjudul Let’s Leran English dapat digunakan sebagai sumber bahan ajar. Penelitian lanjutan tentang efektifitas dari buku teks berjudul “”Let’s Leran English” dapat menjadi perhatian khusus bagi semua kalangan. Kata kunci: evaluasi buku teks, Let’s Learn English